In-stent graft helical flow intensity reduces the risk of migration after endovascular aortic repair. (20th September 2019) - Tasso, Paola; Lodi Rizzini, Maurizio; Raptis, Anastasios; Matsagkas, Mitialdis; De Nisco, Giuseppe; Gallo, Diego; Xenos, Michalis; Morbiducci, Umberto
Abstract: During the last years endovascular aneurysm repair (EVAR) became the elective treatment for abdominal aortic aneurysms (AAAs) thanks to lower mortality and morbidity rates than open surgery. In face of these advantages, stent-graft performances are still clinically suboptimal. In particular, post-surgical complications derive from device migration as a consequence of the hemodynamic forces acting on the endograft. In this regard, while the importance of hemodynamic surface forces is well recognized, the role of the in-stent flow is still unclear. Here we hypothesize that in-stent helical blood flow patterns might influence the distribution of the displacement forces (DF s) acting on the stent-graft and, ultimately, the risk of stent migration. To test this hypothesis, the hemodynamics of 20 post-EVAR models of patients treated with two different commercial endografts was analyzed using computational hemodynamics. The main findings of the study indicate that: (1) helical flow intensity decreases the risk of endograft migration, as given by an inverse correlation between helicity intensity ( h 2 ) and time-averaged displacement forces (TADF s) (p < 0.05); (2) unbalanced counter-rotating helical structures in the legs of the device contribute, in particular along the systole, to significantly suppressTADF s (p < 0.01); (3) as expected, helical flow intensity is positively correlated with pressure drop and resistance to flow (p < 0.001). The findings of this study suggest that a design strategy promoting in-stent helical flow structures could contribute to minimize the risk of migration of implanted EVAR devices.